Síntomas prostáticos y calidad de vida en pacientes antes de ser sometidos a resección transuretral de la próstata. Hospital Víctor Lazarte Echegaray - Trujillo 2002 - Rodríguez Rodríguez, Elsa (2002)
To determine the levels of prostate symptoms and quality of life derived from them in patients diagnosed with Benign Prostatic Hyperplasia before being subjected to TURP in the IV Hospital Víctor Lazarte Echegaray ESSALUD - Trujillo between April and June 2002, this study was carried out of applicative - descriptive type. The results were: the average age of the included patients was 68, 11 ± 7.9, finding that 42.86% of patients belonged to the age group between 70 and 79 years, while 20% had 50 to 59 years old; in the level of prostatic symptoms, 54.29% of the patients presented a moderate level while 45.71% reported a severe level; an IPSS average of 19.06 ± 3.29; in the group of 70 to 79 years 73.33% of the patients presented a severe level of symptoms, 81.81% of the patients from 60 to 69 years had a moderate level of symptoms and 85.71% of the patients from 50 to 59 presented a level moderate symptoms (p <0.05); with respect to the quality of life, 74.29% presented a moderate commitment and 25.71% a severe commitment, also found an average of 4.09 ± 0.82; It was found that of the patients with a moderate level of symptoms, 84.21% presented a moderate commitment to quality of life, while 62.5% of those who presented a severe index of symptoms presented a moderate compromise of quality of life (p> 0.05), also applying the Pearson correlation coefficient was of little correlation